Botanical and Microscopic Characteristics of Morinda officinalis How. in Thua Thien Hue province - Trần, Nam Thắng; Trần, Minh Đức; Hoàng, Thị Hồng Quế; Nguyễn, Hợi; Văn, Thị Yến; Lê, Thái Hùng; Đinh, Diễn; Phạm, Thành; Nguyễn, Ngọc Hoà; Nguyễn, Đình Quỳnh Phú; Nguyễn, Thị Huyền Trang; Huỳnh, Vân Quỳnh; et al. (Hue University Journal of Science: Natural Science, 2023)
Morinda officinalis How. is a medicinal plant that has been studied and used for a long time. Previous studies on M. officinalis primarily focused on the source in the northern provinces of Vietnam. This study is the first one on the botanical characteristics, including morphology, anatomy, and powder microscopy of M. officinalis in Thua Thien Hue province. Morphological and microscopic characteristics were determined by comparing the shape and double-staining and observing under a microscope through 10× and 40× objective lenses. The results show the similarities and differences of M. officinalis in Thua Thien Hue and other regions of Vietnam. Particularly, the root of M. officinalis in Thua Thien Hue has a higher percentage of usable parts than other M. officinalis species in northern regions. Furthermore, the results of the study provide scientific data for learning and investigating the morphological and microscopic characteristics of M. officinalis in Thua Thien Hue.